К выделению нового типа кинжалов позднего бронзового века - Ромашко, В. А. (Давнина. Харківський історико-археологічний щорічник, 2016)
Summary Romashko V. A. Segregation of New Tape of Dagger in Late Bronze Age The paper deals with one of the categories of armors of the late Bronze Age in the Eastern Europe. It is daggers of late timber-grave culture in the Eastern Ukrainian forest-steepe region (XIII-XII centuries B. C). For the first time in Ukrainian archaeology they were typified as Boguslav type. The described type of these daggers does not have analogy among armours of the cultures of Northern Black Sea and Eastern Europe. The author points out that this type can be synchronized with the daggers of so-called Ingoulo-Krasnomayatsky and Sosnovo-Mazinsky types.